Melatonin supplementation attenuates cuproptosis and ferroptosis in aging cumulus and granulosa cells: potential for improving IVF outcomes in advanced maternal age - Kuan-Hao Tsui; Chia-Jung Li; Li-Te Lin (Reproductive Biology and Endocrinology)
Abstract Background Advanced maternal age is associated with decreased oocyte quantity and quality and in vitro fertilization (IVF) success rates. This study aimed to investigate whether melatonin supplementation can improve IVF outcomes in women of advanced maternal age by modulating cuproptosis and ferroptosis. Methods This prospective cohort study included 161 women aged 35–45 years undergoing IVF-frozen embryo transfer cycles. Participants were assigned to either melatonin (n = 86, 2 mg daily for ≥ 8 weeks) or control (n = 75) groups. Cumulus cells were analyzed for cuproptosis and ferroptosis-related gene expression. Additional experiments were conducted on the HGL5 human granulosa cell line to assess mitochondrial function and metabolic reprogramming. Results Melatonin supplementation significantly improved IVF outcomes in women aged ≥ 38 years, increasing clinical pregnancy rates (46.0% vs. 20.3%, P < 0.01), ongoing pregnancy rates (36.5% vs. 15.3%, P < 0.01), and live birth rates (33.3% vs. 15.3%, P < 0.05). In cumulus cells from patients, gene expression analysis revealed that melatonin modulated cuproptosis and ferroptosis-related genes, including ATP7B and GPX4, with more pronounced effects in the ≥ 38 years group. This suggests melatonin enhances cellular resilience against oxidative stress and metal-induced toxicity in the ovarian microenvironment. In vitro studies using HGL5 cells showed melatonin reduced oxidative stress markers, improved mitochondrial function, restored expression of glycolysis and TCA cycle-related genes and modulated cuproptosis and ferroptosis-related gene expression. These findings provide mechanistic insight into melatonin’s protective effects against regulated cell death in ovarian cells, potentially explaining the improved IVF outcomes observed. Conclusions Melatonin supplementation significantly improved IVF outcomes in women of advanced maternal age, particularly those ≥ 38 years old, likely by modulating cuproptosis and ferroptosis and enhancing mitochondrial function in cumulus and granulosa cells. These results suggest that melatonin could be a promising adjuvant therapy for improving IVF success rates in older women.